Karakterisasi Tanaman Padi BC5F1 Hasil Persilangan Padi Varietas Inpari 42 dan Merah Wangi - Deajeng Aldila Permata Noerja (Fakultas Pertanian, 2026)
Rice (Oryza sativa L.) is one of the most important agricultural commodities, as it serves as a staple food for the majority of countries in Asia, including Indonesia. Aromatic rice has gained considerable consumer preference due to its distinctive fragrance, which is attributed to a mutation in the BADH2 gene resulting in the accumulation of 2-acetyl-1- pyrroline (2AP). This study aimed to develop a superior rice variety with an enhanced aromatic trait by introgressing the aromatic BADH2 allele from the Merah Wangi variety into the high-yielding Inpari 42 variety (7.11 tons/ha) using the Marker-Assisted Backcross Breeding (MABB) approach. The resulting BC5F1 population was evaluated for agronomic characteristics and aroma expression. The Bradbury molecular marker was employed to detect the presence of the BADH2 gene mutation. Genotypic analysis of the BC5F1 population identified 31 heterozygous (aromatic) plants. Agronomic evaluation revealed very high uniformity in plant height, days to flowering, panicle length, and 1,000- grain weight. Meanwhile, the total number of tillers per clump, number of productive tillers per clump, number of grains per panicle, and filled grain weight per clump exhibited moderate variability. In contrast, the percentage of unfilled grains per panicle showed relatively high variation. Based on these findings, the BC5F1 lines demonstrate potential for further advancement in subsequent generations to obtain individuals with greater uniformity and genetic stability.
FINALISASI oleh Arif 2026 Mei 19
Keywords: Rice plants; aromatic rice; backcrossing